Expression of a proteolipid gene from a high-copy-number plasmid confers trifluoperazine resistance to Saccharomyces cerevisiae. - Shih, C K (1990)
A wild-type haploid yeast strain was transformed with a library of wild-type yeast DNA fragments ligated into a high-copy-number plasmid vector (YEp24). The pooled URA+ transformants were plated on rich medium containing a lethal concentration of trifluoperazine (TFP). Plasmids rescued into Escherichia coli from TFP-resistant yeast colonies contained overlapping DNA fragments from a unique region of yeast chromosome XVI. Deletion and disruption experiments, mini-Tn10 LUK hop analysis, and DNA sequencing defined a novel gene with significant amino acid identity to bovine and yeast vacuoletype proteolipid subunits. This is the second locus identified that can be altered to confer TFP resistance to Saccharomyces cerevisiae and that has significant amino acid identity to a vacuolar ATPase subunit. This suggests that a target for TFP in S. cerevisiae is the electrogenic membranes of the vacuolar network and that alteration of expression or activity of vacuolar proton ATPase subunits is a general mechanism for TFP resistance in this yeast.